PSYCHOLOGICAL EFFECTS OF COLOR AND COLOR THERAPY: रंगो का मनोवैज्ञानिक प्रभाव एवं रंग चिकित्सा - Kumar Gupta, Ajay (International Journal of Research -GRANTHAALAYAH, 2014)
Many opinions about colors are popular, but most of the artists nowadays follow the opinion of Aust Wald, according to their opinion, the main colors are yellow, red, blue and green, these are four and the ideal color is eight. The first four colors are called primordial (vatpahdans) colors and the second four i.e. purple, sky, orange and dhani are called second colors (Aambavadakantal). Apart from this, there are three colors and black, white, khaki (oval), these are called neutral colors (chamanjatans), they are mostly used to decrease and increase the color of other colors. The psychological impact of these colors has on human life, which has been considered the origin of colors on this Vasundhara since the birth of creation. Since ancient times, there have been different beliefs in terms of colors, such as red color - passion and revolution, black color - inauspicious, negative, green color - optimism brings happiness, blue color - peace, white color - purity brings reconciliation etc. Through colors on the canvas of paintings, the artist, in his silent language, shapes happiness, pain, agony with his imaginations and transmits his feelings to another. These pictures have many colors, we just have to understand them. There are many colors in nature which awaken the feeling of happiness in our mind and provide new energy. In today's time, imagining a world without colors for a moment is not only difficult. While colors have a special place in life, in the world, whatever we see with our eyes, the effect of color is first visible because many colors are present in the world. रंगों के विषय में अनेक मत प्रचलित है पर आजकल के अधिकांश कलाकार आस्ट वाल्ड के मत को ही मानते है इनके मतानुसार मुख्य रंग पीला, लाल, नीला और हरा ये चार होते है और आदर्श रंग आठ होते है। प्रथम चार रंगों को मौलिक (व्तपहदंस) रंग कहते है और दूसरे चार अर्थात बैगनी, आसमानी, नारंगी और धानी को द्वितीय रंग (ैमबवदकंतल) कहते है। इनके अतिरिक्त तीन रंग और है काला, सफेद, खाकी (ळतंल) इनको तटस्थ रंग (छमनजतंस) कहते है इनका प्रयोग अधिकतर अन्य रंगों की सुषमा (ज्वदम) को घटाने और बढ़ाने में किया जाता है। इन्ही रंगों का मनौवैज्ञानिक प्रभाव मानव जीवन पर पड़ता है जो सृष्टि के जन्म से ही इस वसुन्धरा पर रंगो की उत्पत्ति का प्रार्दुभाव माना गया है। प्राचीनकाल से ही रंगो के संदर्भ में अलग-अलग मान्यतायें रही है जैसे लाल रंग - जोश एवं क्रांति, काला रंग - अशुभ, अनिष्ट, हरा रंग- आशावादिता खुशहाली, नीला रंग - शान्त, सफेद रंग - पवित्रता सुलह आदि का परिचय देता है। रंगो के माध्यम से चित्रों के कैनवास पर कलाकार अपनी मौन भाषा में खुशी, पीड़ा, व्यथा को अपनी कल्पना शक्ति से आकार प्रदान कर अपनी भावनाओं को दूसरे तक पहुंचाता है। इन चित्रों के अनेक रंग रूप होते है, हमें सिर्फ उन्हें समझना पड़ता है। प्रकृति में बहुत से रंग है जो हमारे मन में खुशी की भावना जागृत कर नई उर्जा प्रदान करते है। आज के समय में क्षण भर के लिए बिना रंगों के संसार की कल्पना कठिन ही नही असम्भव है। जहां रंगों का जीवन में विशिष्ट स्थान है वहीं संसार में हम अपनी आंखों से जो कुछ भी देखते है उनमें सबसे पहले रंग का प्रभाव दृष्टिगोचर होता है क्यांेकि सृष्टि में अनेकों रंग विधमान है।